Prediction of posttraumatic stress in fathers of children with chronic diseases or unintentional injuries: a six-months follow-up study - Sennhauser Felix H; Vollrath Margarete E; Ribi Karin; Gnehm Hanspeter E; Landolt Markus A (BMC, 2007)
Abstract Background While fathers were neglected for a long time in research investigating families of pediatric patients, there are now a few studies available on fathers' posttraumatic stress symptoms (PTSS) and posttraumatic stress disorder (PTSD). However, little is known about the course of PTSS and PTSD in fathers of pediatric patients. The present study aimed to compare the prevalence and course of PTSS and PTSD in fathers of children with different chronic and acute conditions and to identify factors that contribute to fathers' PTSS. Methods Sixty-nine fathers of children newly diagnosed with either cancer, type I diabetes mellitus, or epilepsy and 70 fathers of children suffering from an unintentional injury completed questionnaires at 4-6 weeks (Time 1) and six months (Time 2) after diagnosis or injury. Results Noticeable PTSD rates were found in fathers of children with a chronic disease (26% at Time 1 and 21% at Time 2, respectively). These rates were significantly higher than rates found in fathers of children with unintentional injuries (12% at Time 1 and 6% at Time 2, respectively). Within six months after the child's diagnosis or accident a decrease in severity of PTSS was observed in both groups. Significant predictors of PTSS at Time 2 were the father's initial level of PTSS, the child's medical condition (injuries vs. chronic diseases) and functional status, the father's use of dysfunctional coping strategies, and father's level of neuroticism. Conclusion Our findings suggest that fathers with initially high PTSS levels are at greater risk to experience PTSS at follow-up, particularly fathers of children with a chronic disease. Sensitizing health care professionals to the identification of PTSS symptoms but also to indicators of neuroticism and the use of specific coping strategies early in the treatment course is essential for the planning and implementation of adequate intervention strategies.